2016
DOI: 10.1016/j.physleta.2016.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the noise in dynamical reduction models

Abstract: The dynamics of a quantum system with internal degrees of freedom undergoing spontaneous collapse in the position basis are analysed; e.g., neutral mesons or neutrinos. Surprisingly, the value of the Heaviside function θ(x) at x = 0 that can in general be chosen in the interval [0,1] leads to different physical predictions. For the QMUPL (Quantum Mechanics with Universal Position Localization) model only a single value leads to probabilities conserving the particle number. Herewith the physical properties of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Now, we turn to the collapse models acting in the Hilbert space L 2 (R d ) ⊗ H M with d = 1, 2, 3, which combines the position and flavor spaces, and the collapse is assumed to the spatial part of the state of the system. For the sake of concreteness, we consider the QMUPL and the mass-proportional CSL models, which were widely analyzed in the context of flavor oscillations [51][52][53][54][55][56], and generalize them to the models with the time-asymmetric noise field. In this way, we analyze the quantum state equation…”
Section: Qmupl and Csl Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, we turn to the collapse models acting in the Hilbert space L 2 (R d ) ⊗ H M with d = 1, 2, 3, which combines the position and flavor spaces, and the collapse is assumed to the spatial part of the state of the system. For the sake of concreteness, we consider the QMUPL and the mass-proportional CSL models, which were widely analyzed in the context of flavor oscillations [51][52][53][54][55][56], and generalize them to the models with the time-asymmetric noise field. In this way, we analyze the quantum state equation…”
Section: Qmupl and Csl Modelsmentioning
confidence: 99%
“…It has been put under discussion whether the spontaneous collapse can be considered also as a source of the particle decay [54][55][56]. It has been shown that the decay dynamics can be recovered by the mass-proportional CSL model with an asymmetric correlation function of the noise field underlying this collapse model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gives the dominant interaction term λ X (t) x (t) 3 . The lowest contribution of this term yields the two-loop quantum effect for X (t)…”
Section: Ctp To Langevinmentioning
confidence: 99%
“…There is no explicit observer nor detector in the early Universe and therefore quantum mechanics cannot yield any definite outcome of the quantum fluctuations. In order to solve this problem, some authors introduce detectors [1] [2]or modify the basic laws of quantum mechanics so that the wave function spontaneously collapses [3]. This situation is similar to the quantum-information-theory aspect of the black hole [4].…”
Section: Introductionmentioning
confidence: 99%